2019
DOI: 10.1007/978-1-4939-9136-5_16
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Lipid-Binding Specificity of SMP Domains: An ERMES Subunit as a Case Study

Abstract: Membrane contact sites between the endoplasmic reticulum (ER) and mitochondria function as a central hub for the exchange of phospholipids and calcium. The yeast Endoplasmic Reticulum–Mitochondrion Encounter Structure (ERMES) complex is composed of five subunits that tether the ER and mitochondria. Three ERMES subunits (i.e., Mdm12, Mmm1, and Mdm34) contain the synaptotagmin-like mitochondrial lipid-binding protein (SMP) domain. The SMP domain belongs to the tubular lipid-binding protein (TULIP) superfamily, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…To study lipid binding, His-tagged CLDP43 (CLDP43-His) and the C2 domain of lactadherin (C2-His), as control protein with known lipid binding properties [59][60][61], were expressed in E. coli, purified and analyzed by SDS-PAGE and immunoblotting (Fig 5A). [62,63]. However, despite multiple attempts, we were unable to detect binding of CLDP43-His, or C2-His, to liposomes composed of PC:PE (80:20%), PC:PE:PS, PC:PE:PA or PC:PE:CL (70:10:20%, for all three liposome compositions).…”
Section: Recombinant Cldp43 Binds Pa and CL In Vitromentioning
confidence: 73%
“…To study lipid binding, His-tagged CLDP43 (CLDP43-His) and the C2 domain of lactadherin (C2-His), as control protein with known lipid binding properties [59][60][61], were expressed in E. coli, purified and analyzed by SDS-PAGE and immunoblotting (Fig 5A). [62,63]. However, despite multiple attempts, we were unable to detect binding of CLDP43-His, or C2-His, to liposomes composed of PC:PE (80:20%), PC:PE:PS, PC:PE:PA or PC:PE:CL (70:10:20%, for all three liposome compositions).…”
Section: Recombinant Cldp43 Binds Pa and CL In Vitromentioning
confidence: 73%
“…1d ). To clarify whether MIGA2 is involved in extracting phospholipids from liposomes, we performed lipid extraction as described in a previous study 12 , 15 . The results confirmed that mMIGA2 313–570 can extract NBD-PE from liposomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, we propose that MIGA2 plays a key role in transporting pan-phospholipids at the ERMCS. Likewise, in yeast, the ERMES complex transfers a wide spectrum of phospholipids substrates between the ER and mitochondria, although it has no obvious selectivity toward certain phospholipids [11][12][13][14][15] . Since the conversion of PS to PE occurs in mitochondria and PE is a substrate for generating PC, the transport of phospholipids between ER and mitochondria would be essential for maintaining phospholipids homeostasis in cells 6,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lipid transfer functions of many of the proteins described here have been dissected using in vitro systems with liposomes used as donor and acceptors of fluorescent lipids to monitor their LTP-mediated transfer either by dequenching or quenching of fluorescence; liposome flotation has also been used to characterize the affinity of LTP for membranes of specific compositions. Studies of the SMP domains of E-SYT2 ( Saheki et al, 2016 ), Mdm12 and Mmm1 in ERMES ( Jeong et al, 2017 ; Kawano et al, 2017 ; AhYoung and Egea, 2019 ), the Ups1/Mdm35 ( Watanabe et al, 2015 ) and also Osh6 ( Maeda et al, 2013 ; Moser von Filseck et al, 2015 ) and OSBP ( Mesmin et al, 2013 ) are examples of these approaches. Other studies have used partially purified intact membrane fractions to monitor lipid transfer ( Kojima et al, 2016 ) or genetic and mutagenesis methods combined to lipidomics to study the effect of lipid biosynthesis rewiring on the levels and distributions of cellular lipids in the network of organelles ( John Peter et al, 2021 ; Peter et al, 2021 ).…”
Section: Vectoring and Energizing Lipid Exchange At Membrane Contact Sites And Within Membranes: “Passive” Versus “Actmentioning
confidence: 99%